Enter Xiuhquilitl: indigo in the Spanish Empire, c.1550-1700 - Catena, A (2015)
Over the course of the sixteenth century, the burgeoning globalising forces of exploration and discovery transformed the indigo trade in Asia and the Americas, the histories of blue, and woad producing regions in Europe. Around 1560, the Spanish Crown found indigo-producing plants grew wild in parts of New Spain, and across the Captaincy General of Guatemala; settlers turned with enthusiasm to the new industry, and by 1600 indigo ranked third on the list of exports from the Spanish colonies – after bullion, and cochineal, contending for its place with cattle hides. Previous studies of colonial Mesoamerican indigo have concentrated on eighteenth century production methods and the problematic of indigenous labour, rarely following the blue dye past the port of Seville, to the dyer’s vat or the artist’s studio. Processes of reception, accommodation (sometimes rejection), and commodification, the initial development of manufacturing techniques and the diffusion of these new practices, have been left unexamined. This thesis seeks to address some of these, neglected chapters in the history of indigo, constructing a narrative that integrates the experiences of producers and consumers, considering the materiality of indigo (in its raw, and multiple finished forms). Drawing on selected case studies from across the Empire, I examine the production, trade, and consumption of New World indigo over the course of two centuries – between 1550 and 1750 – focusing on the individuals and groups, connections and interactions that determined its path from an unfamiliar, exotic dye, to a commodity circulated globally.